Ukraine : Request for Stand-By Arrangement-Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Ukraine's Request for a Stand-By Arrangement (SBA). The authorities have requested a 12-month SBA, which they intend to treat as precautionary. Their economic program for 2004 aims to sustain recent stabilization gains and advance some important structural reforms. Key objectives are to support economic growth; keep inflation under control; bolster debt sustainability; maintain an adequate level of international reserves; reduce credit risk in the banking sector; and improve the investment climate, including through wide-ranging tax reforms.